2022
DOI: 10.1111/1750-3841.16037
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and enzymatic hydrolysis of radio frequency cold plasma treated starches

Abstract: The effect of carbon dioxide‐argon radio frequency cold plasma treatment on the in vitro digestion and structural characteristics of granular and non‐granular waxy maize, potato, and rice starches was investigated in this study. The effect on the fine structure of waxy potato was very minimal after plasma treatment irrespective of their granular or non‐granular form. The short chain length (SCL) of waxy maize and rice (granular and non‐granular) starches was reduced leading to subsequent increases in the long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…The authors reported that higher plasma power levels and longer treatment times resulted in the cleavage of hydrogen bonds in starch, thus decreasing the intensity of the H–O–H bending vibration peaks ( Sudheesh et al, 2019 ). Okyere et al (2022) reported the ability of a radio frequency plasma to induce cross-linking in non-granular waxy maize and rice as well as granular waxy potato and rice starches as shown by Fourier Transform Infrared-Attenuated total reflectance (FTIR-ATR) analysis. The authors also reported minor changes in waxy starches' unit and internal chain structure after RF plasma modification.…”
Section: Starch Modification Using Cold Plasmamentioning
confidence: 99%
“…The authors reported that higher plasma power levels and longer treatment times resulted in the cleavage of hydrogen bonds in starch, thus decreasing the intensity of the H–O–H bending vibration peaks ( Sudheesh et al, 2019 ). Okyere et al (2022) reported the ability of a radio frequency plasma to induce cross-linking in non-granular waxy maize and rice as well as granular waxy potato and rice starches as shown by Fourier Transform Infrared-Attenuated total reflectance (FTIR-ATR) analysis. The authors also reported minor changes in waxy starches' unit and internal chain structure after RF plasma modification.…”
Section: Starch Modification Using Cold Plasmamentioning
confidence: 99%
“…The chain-length distribution of the produced maltodextrin was determined as outlined by Okyere et al (2022) , with adjustments in sample preparation. Maltodextrin (2.0 mg) was dissolved in 90% DMSO (100 μL), in septuplicate, and stirred overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of rapidly digestible starches increased in granular waxy maize starch (WMS G) (85.08%) but was unaffected in non-granular waxy rice (WRS NG), WPS G, and non-granular waxy potato starches after plasma treatment. Okreye et al [ 142 ] Cashew Glow discharge plasma (low-pressure) The plasma processing decreased the amount of sucrose and increased the fatty acids and glycerol (made them more available) regardless of the time and flow rate of the synthetic air. Alves Filho et al [ 143 ]
Fig.
…”
Section: T-2 and Ht-2 Toxinsmentioning
confidence: 99%
“…Changes in its rheological properties tend to transition from pseudoplastic (non-Newtonian) fluids to Newtonian fluids. Okyere et al [ 142 ] studied the effects of carbon dioxide-argon RF CP treatment on the in vitro digestion and structural characteristics of granular and non-granulated waxy maize, potato, and rice starch, and observed that plasma treatment could also change the damaged starch content, making the relative number of short chains decrease, resulting in a slight increase in long chains. The treated starch is beneficial to slow the release of glucose in the blood and affects the in vitro digestibility of starch, which certainly improves the quality of starch.…”
Section: T-2 and Ht-2 Toxinsmentioning
confidence: 99%